1990
DOI: 10.1111/j.1651-2227.1990.tb11484.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Tract Infections in Children

Abstract: Respiratory tract infections (RTIs) in small children account for a considerable proportion of health care expenditure. In 113 children, followed for the first three years of life, we studied the frequency of acute RTI and its relationship to the factors: type of day-care, age, sex, family size, living conditions, allergic predisposition, family smoking habits, and season. To elucidate the influence of age, the frequency of acute RTI and its relationship to type of day-care was longitudinally studied on a quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…15 Other reports for children under 2 years of age have also documented failure rates of 15% despite treatment with antimicrobials. 9,34,35 In the current study, children between 2 and 5 years of age had higher clinical resolution rates (87.2% and 96.9%) with larger absolute differences (9.7%) between placebo and amoxicillin, which may reflect a higher degree of certainty in diagnosis of bacterial acute otitis media in this age group. Another placebo-controlled trial reported a 5% absolute difference among children over 2 years of age and a 3.3% difference among those under 2 years of age.…”
Section: Discussionmentioning
confidence: 49%
“…15 Other reports for children under 2 years of age have also documented failure rates of 15% despite treatment with antimicrobials. 9,34,35 In the current study, children between 2 and 5 years of age had higher clinical resolution rates (87.2% and 96.9%) with larger absolute differences (9.7%) between placebo and amoxicillin, which may reflect a higher degree of certainty in diagnosis of bacterial acute otitis media in this age group. Another placebo-controlled trial reported a 5% absolute difference among children over 2 years of age and a 3.3% difference among those under 2 years of age.…”
Section: Discussionmentioning
confidence: 49%
“…The highest proportion is found in densely populated areas. Viral infections have been shown to be more common in children with regular attendance in day-care centres in Sweden and other countries (Strangert, 1976;Anderson et al, 1988;Petersson and Hakanson, 1989;Harsten et al, 1990). A difference in hospital admission in urban and rural areas for respiratory tract infections in children has been shown in Denmark (Moltesen and Hjuler, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent infections of the upper respiratory tract (rURTI [2][3][4] were defined as at least four 3-monthly episodes with an ear infection and/ or throat infections and/or at least six episodes with a severe common cold. Recurrent infections of the upper respiratory tract between ages 4 and 8 years (rURTI [4][5][6][7][8] were defined as the occurrence of four or more ear infections and/or four or more throat infections and/ or six or more severe common colds.…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…[1][2][3] These infections not only have an impact on children's health and well-being, but also generate high medical costs and indirect costs for the family and the society. 4,5 Children experience, on average, 4-6 URTIs per year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation